2013
DOI: 10.3389/fncel.2013.00144
|View full text |Cite
|
Sign up to set email alerts
|

Fatting the brain: a brief of recent research

Abstract: Fatty acids are of paramount importance to all cells, since they provide energy, function as signaling molecules, and sustain structural integrity of cellular membranes. In the nervous system, where fatty acids are found in huge amounts, they participate in its development and maintenance throughout life. Growing evidence strongly indicates that fatty acids in their own right are also implicated in pathological conditions, including neurodegenerative diseases, mental disorders, stroke, and trauma. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 123 publications
3
63
0
Order By: Relevance
“…Briefly, fatty acids are classified based on the number of double bonds (i.e., the degree of saturation/unsaturation) in the carbon chain into saturated (SFA; no double bonds), monounsaturated (MUFA; one double bond), or polyunsaturated (PUFA; two or more double bounds) [13]. PUFAs are further distinguished based on the position of the first double bond from the methyl terminal end into n -3 or n -6 PUFAs.…”
Section: Overview Of Dietary Fatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, fatty acids are classified based on the number of double bonds (i.e., the degree of saturation/unsaturation) in the carbon chain into saturated (SFA; no double bonds), monounsaturated (MUFA; one double bond), or polyunsaturated (PUFA; two or more double bounds) [13]. PUFAs are further distinguished based on the position of the first double bond from the methyl terminal end into n -3 or n -6 PUFAs.…”
Section: Overview Of Dietary Fatsmentioning
confidence: 99%
“…This is notable given that brain insulin resistance promotes depression-like behavior in rodents [45]. Furthermore, low MUFA levels have been associated with the development of Alzheimer’s disease, as suggested by findings that MUFA levels, especially oleic acid, are reduced in the brain of Alzheimer’s patients [13]. Importantly, depression is commonly observed in Alzheimer’s patients [46].…”
Section: Dietary Fat Regulation Of Brain Function and Links To Depmentioning
confidence: 99%
“…Indeed, lipid accumulations were one of the five original AD-associated tissue pathologies reported by Alois Alzheimer (Alzheimer, 1907). More recently, links have strengthened between aberrant lipid metabolism and neurodegeneration in AD (Astarita et al, 2011;Fraser et al, 2010;Hussain et al, 2013;Podtelezhnikov et al, 2011;Tanzi, 2012), while epidemiological studies have demonstrated that AD risk factors include peripheral metabolic conditions such as insulin resistance, obesity, and dyslipidemia (Pasinetti and Eberstein, 2008). However, deeper mechanistic insights into the role of abnormal lipid metabolism in AD have been hindered by the technical complexity involved with localizing, identifying, and determining the biological functions of individual lipid species in the brain.…”
Section: Introductionmentioning
confidence: 97%
“…These results demonstrate that the presence of an alternative food option does not influence the ability of baclofen to reduce shortening intake. Why consumption of shortening and lard would be differentially affected by baclofen under the experimental conditions reported here is not clear, but may be due to the differential fatty acid composition of the two fats (Hussain et al, 2013). Future studies will need to be conducted in which dietary fatty acid composition is systematically manipulated and effects on baclofen pharmacokinetics and pharmacodynamics are assessed.…”
Section: Discussionmentioning
confidence: 93%